FAKTOR-FAKTOR YANG MEMPENGARUHI RENDAHNYA PRESTASI BELAJAR UJIAN MATEMATIKA SISWA DENGAN MENGGUNAKAN METODE ANALISIS FAKTOR - Efrasia Nasri; Taba Heri Setiawan; Hendro Warianto; Aden Aden; Ilmadi Ilmadi (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
The purpose of this study is to know the factors affecting the low achievement of student mathematical learning throught the reduction process. In this study The Factor Analysis Method is used with Principal Component Analysis. Based on the research correlation value, there are 5 highest factor thet affect the low learning achievement of students’ mathematics tests, namely, faktor 1 correlates 0,550 consisting of instrumental factors and social environmental factors. The factors 2 correlates 0,750 which consists of motivation and interst. The factors 3 correlates 0,564 which consist of the school social environmental, physical tone and family social environmental. The factor 4 correlates -0,623 which consists of the social environment of the community, mistaken and the state of physical function. And factor5 correlate 0,570, which is intelligence. And also, the more dominant factors in teaching and learning activietes in mathematics, namely factor 1 which has a variance of 30,15% formed by internal and external factors that influence the learning process in mathematics in Mekar Lestari Orphanage